STRATEGI KONSERVASI UNTUK MENGURANGI EROSI HULU DAERAH ALIRAN SUNGAI BRANTAS, JAWA TIMUR - Pambudi, Andi Setyo; Junaidi, Rahmat; Pramujo, Bambang (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2023)
Sedimentation caused by erosion in the Lesti Sub-Watershed and the upstream part of the Brantas Watershed as a whole has an impact on disrupting the role of the Sengguruh Dam in supporting economic activity in East Java. Reducing erosion in upstream areas during their development requires an environmental science approach that harmonizes economic, social, and environmental aspects. This study aims to: Assess the influence of population pressure, community behavior, and land use on erosion in the Lesti Sub-watershed; Predict erosion in the Lesti Sub-watershed; and Provide an environmental science-based conservation strategy for the Lesti Sub-watershed in the context of sustainable development.. The research method used was mixed methods, both through GIS assistance for the Modify Universal Soil Loss Equation erosion formula and also through questionnaires and interviews with communities in the Lesti sub-watershed area. From research on the Lesti sub-watershed, the average erosion rate obtained is 153,868 tons/ha/year, which means it exceeds the minimum tolerance limit. Of the 12 sub-districts in the Lesti sub-watershed area, 6 (six) sub-districts have problems from the environmental aspect through the condition of several sub-districts with high erosion hazard levels. Erosion is correlated with people's knowledge, attitudes, and behavior in the economic aspects through population pressure and social conditions through land use patterns. Based on environmental science, conservation priority recommendations are for these 6 (six) sub-districts by improving soil and water conservation efforts, both vegetatively and civil-technically (environmentally), environmental education (social), and community economic empowerment (economy).